Antibodies against Apoptotic Cells Present in End-stage Lung Disease Patients Do Not Correlate with Clinical Outcome after Lung Transplantation - Budding, Kevin; van de Graaf, Eduard A.; Kardol-Hoefnagel, Tineke; Oudijk, Erik-Jan D.; Kwakkel-van Erp, Johanna M.; Hack, C. Erik; Otten, Henny G. (Frontiers in Immunology, 2017)
Antibodies against HLA and non-HLA are associated with transplantation outcome. Recently, pre-transplant serum IgG antibody levels against apoptotic cells were found to correlate with kidney allograft loss. We investigated the presence of these antibodies in lung transplantation (LTx) patients and evaluated the correlation of pre-LTx serum levels of IgG antibodies against apoptotic cells with LTx outcome. These cells included donor lung endothelial cells (EC) obtained from lung perfusion fluid collected during LTx procedure. Cells were isolated, expanded in vitro, and analyzed as targets for anti-apoptotic cell reactivity. Cultured cells exhibited EC morphology and were CD31+, CD13+ and vWF+ . End-stage lung disease patients showed elevated serum IgG levels against apoptotic lung EC (p=0.0018) compared to healthy controls. Interestingly, the levels of circulating antibodies directed against either apoptotic Jurkat cells or apoptotic lung EC did not correlate, suggesting a target cell specificity. We observed no correlation between chronic or acute rejection and pre-LTx serum levels of anti-apoptotic antibodies. Also, these levels did not differ between matched patients developing chronic rejection or not during follow-up or at the time of diagnosis, as they remained as high as prior to transplantation. Thus, circulating levels of anti-apoptotic cell antibodies are elevated in end-stage lung disease patients but our data do not correlate with outcome after LTx.